Case report: a transcatheter aortic valve replacement failure secondary to COVID-19 infection. Issue 2 (31st January 2023) - Tacon, P Ryan; Cao, Louie; Birkeland, Kade; Kedan, Ilan
Abstract: Background: Valve thrombosis is a well-documented cause of bioprosthetic valve failure. Case reports have been published of prosthetic valve thrombosis secondary to COVID-19 infection. This is the first case report of COVID-19 associated valve thrombosis in a patient with transcatheter aortic valve replacement (TAVR). Case summary: A 90-year-old female with atrial fibrillation on therapeutic apixaban and status-post TAVR presented with COVID-19 infection and was found to have severe bioprosthetic valvular regurgitation with features suggestive of valve thrombosis. She underwent valve-in-valve TAVR with resolution of valvular dysfunction. Discussion: This case report contributes to a growing body of evidence describing the occurrence of thrombotic complications in patients with valve replacement and COVID-19 infection. Increased vigilance and continued investigation are warranted to better characterize thrombotic risk and to inform optimal antithrombotic strategies during COVID-19 infection.